Evolution of P[8], P[4], and P[6] VP8* genes of human rotaviruses globally reported during 1974 and 2017: possible implications for rotavirus vaccines in development - Daniel E. Velasquez; Baoming Jiang (Taylor & Francis Group, 2019)
Non-replicating parenteral rotavirus (RV) vaccine candidates are in development in an attempt to overcome the lower efficacy and effectiveness of oral RV vaccines in low-income countries. One of the leading candidates is a truncated recombinant VP8* protein, expressed in Escherichia coli from original sequences of the prototype RV genotypes P[8], P[4], or P[6] isolated before 1983. Since VP8* is highly variable, it was considered useful to examine the evolutionary changes of RV strains reported worldwide over time in relation to the three P2-VP8 vaccine strains. Here, we retrieved from the GenBank 6,366 RV VP8* gene sequences of P[8], P[4], or P[6] strains isolated between 1974 and 2017, in 77 countries, and compared them with those of the three P2-VP8 vaccine strains: Wa (USA, 1974, G1P[8]), DS-1 (USA, 1976, G2P[4]), and 1076 (Sweden, 1983, G2P[6]). Phylogenetic analysis showed that 94.9% (4,328/4,560), 99.8% (1,141/1,143), and 100% (663/663) of the P[8], P[4], and P[6] strains, respectively, reported globally between 1974 and 2018 belong to non-vaccine lineages. These P[8], P[4], and P[6] RV strains have a mean of 9%, 5%, and 6% amino acid difference from the corresponding vaccine strains. Additionally, in the USA, the mean percentage difference between all the P[8] RV strains and the original Wa strain increased over time: 4% (during 1974-1980), 5% (1988-1991), and 9% (2005-2013). Our analysis substantiated high evolutionary changes in VP8* of the P[8], P[4], and P[6] major RV strains and their increasing variations from the candidate subunit vaccine strains over time. These findings may have implications for the development of new RV vaccines.